Clinical toxicology of beta‐blocker overdose in adults. Issue 2 (15th April 2019) - Lauterbach, Michael
Abstract: Beta‐blocker overdose is potentially harmful due to the strong blood pressure‐lowering and heart rate‐lowering effects. However, conflicting data exist as to their differential toxicity, single‐substance exposures and the effect of co‐exposure with additional antihypertensive medication. For this, a 10‐year retrospective, explorative analysis of the Mainz Poison Center/Germany database with regard to circumstances of beta‐blocker exposure, doses, symptoms and treatment was carried out. Analyses were restricted to adult patients with single‐substance exposures and co‐exposures with one additional antihypertensive substance. Written follow‐up information was obtained in half the cases. A total of 2967 cases were analysed, of which 697 were single‐substance exposures. Metoprolol was most frequently reported followed by bisoprolol, atenolol, propranolol and sotalol. Metoprolol showed a linear dose‐symptom relationship, whereas propranolol and sotalol seemed to have a threshold dose beyond which symptoms aggravated. Symptoms did not differ substantially, except for more seizures being reported with propranolol, and more CNS depression/vomiting with sotalol. Activated charcoal was used in 38%, gastric lavage in 11%, temporary pacemaker in 3%, glucagon in 1%, intubation for respiratory insufficiency and cardiopulmonary resuscitation in 1% and 0.5%. All patients recovered. In 174 co‐exposure cases, the distribution of poisoning severity and rate of worsening of symptoms was comparable with single‐substance exposures except one patient deceased after bisoprolol and verapamil co‐exposure. In adults with beta‐blocker overdose, no significant differences in poisoning severity among beta‐blockers were detected, and no fatalities were observed with single‐substance exposures. Co‐exposures with other antihypertensives, sedatives or alcohol should be carefully attended to as fatalities might occur.